Pengaruh pH Saliva terhadap Kelarutan Ion Aluminium Pada Resin Komposit Nanohybrid - Aufia Espressivo; Dyah Irnawati; Purwanto Agustiono (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
Nanohybrid composite resin is a type of composite resin restorative material containing micro-sized filler particles incorporated with nanoparticles. Composite resin restoration in the oral cavity can release its filler particles, one of them is aluminum ion. The pH of saliva is varied. This research aimed to determine the influence of salivary pH on aluminum ion solubility of nanohybrid composite resin. The materials used were nanohybrid composite resin Tetric Evoceram (Ivoclar Vivadent, Austria) and artificial saliva with pH of 5.6, 6.7, and 8.0. Twelve disc-shaped composite resin samples sized 5 mm in diameter and 2 mm thick were made. Samples were polymerized using light curing unit for 20 seconds. Composite resin samples were divided into three pH groups (n=4) and then each sample was soaked in 10 mL artificial saliva inside of polyethylene bottle. The immersion was done in the incubator for 14 days at 37ºC. The concentration of aluminum ion in artificial saliva solutions subsequently was calculated using AAS. Data were analyzed using One-way ANOVA (a=0,05). The mean concentration of aluminum ion released into saliva with pH 5.6, 6.7, and 8.0 were 0.538 ± 0.996 ppm, 0.431 ± 0.981 ppm, and 0.350 ± 0.071 ppm respectively. The result of One-way ANOVA showed a significant influence of salivary pH variation to the solubility of aluminum ion on nanohybrid composite resin (p<0,05). LSD test showed a significant difference only between saliva pH 5,6 and 8,0. The conclusion of this research was that low salivary pH increased the solubility of aluminum ion on nanohybrid resin composite in saliva.